RADIATION NECROSIS AFTER CAVERNOMA RADIOSURGERY SIMULATING BRAIN HIGH-GRADE GLIOMA - A CASE REPORT AND REVIEW OF THE LITERATURE - Radoslav Georgiev (Peytchinski Publishing, 2023)
We report a 62-year-old female patient who came to our institution due to pain and limited movements in the neck area, nausea, and headache. The magnetic resonance imaging (MRI) revealed a single larger and two smaller lesions with the appearance of cavernomas in the left parietal brain region. The patient was consulted with a neurosurgeon and was judged to be inoperable. Radiosurgery was performed in ​​the cavernoma with a total focal dose of 15Gy. 11 months after the radiotherapy, during a routine follow-up MRI scan, a tumor-like lesion with extensive perifocal edema and midline dislocation, with heterogenous structure and ring-like enhancement was reported in the left parietal brain region. After follow-up for 15 months, the last MRI showed almost complete reverse development of the described lesion, with marked reduction of volume, edema, and contrast enhancement. Along with MRI features of the lesion, some of which overlap with high-grade glioma characteristics, the evolution of the lesion is in favor of a radiation necrosis zone.